Immune system stimulation induced by Escherichia coli lipopolysaccharide alters plasma free amino acid flux and dietary nitrogen utilization in growing pigs. (17th October 2018) - McGilvray, Whitney D; Klein, David; Wooten, Hailey; Dawson, John A; Hewitt, Deltora; Rakhshandeh, Amanda R; de Lange, Cornelius F M; Rakhshandeh, Anoosh
Abstract: Changes in plasma free AA flux reflect the modification of AA metabolism in different metabolic states. Immune system stimulation (ISS ) in growing pigs may redistribute AA from protein retention towards processes involved in the immune response, thus impacting AA utilization. The aim of the current study was to evaluate the effect of ISS on whole-body nitrogen (N) utilization and the kinetics of plasma free AA. Ten gilts (BW 9.4 ± 1.1 kg) were surgically fitted with jugular vein catheters, individually housed in metabolism crates, and feed-restricted (550 g/d). Repeated intramuscular injections of increasing amounts of Escherichia coli lipopolysaccharide (LPS ) were used to induce ISS (30 and 36 µg/kg BW, given 48 h apart). Whole-body N-balance was determined for 3-d before ISS (ISS−) and 3-d during ISS (ISS+). At the end of each N-balance period, a bolus dose of labeled [U- 13 C, U- 15 N]-AA mixture (Ile, Leu, Lys, Met, Phe, Thr, Trp, Val, and Gln) was infused intravenously, followed by serial blood collection for determination of isotopic enrichment. A double exponential model was fitted with plasma enrichment data for each pig and each AA, and equation parameters were used to estimate plasma-free AA flux and pool size. Apparent ileal digestibility (AID ) of N was determined using the slaughter technique and an indigestible marker. Blood samples were collected before and 76-h after the initiation of ISS and assayed for hematology and blood chemistry. Body temperature (BT ) was monitored during the course of study. Blood chemistry, hematology, and BT results indicated that LPS induced effective ISS in pigs ( P < 0.05). ISS tended to reduce N retention ( P = 0.09) and the N retention-to-N intake ratio ( P = 0.08). Apparent total tract digestibility of dietary energy and AID of N were reduced by ISS ( P < 0.05). Plasma flux (µmol/kg BW/h) for Ile and Phe was reduced by ISS ( P < 0.05). Strong tendencies for decreased Lys flux and N retention were observed in ISS pigs ( P < 0.10). ISS increased the pool size for Leu but reduced the pool size for Ile ( P < 0.05). Collectively, these results suggest that ISS alters the utilization of dietary N and AA flux, as well as pool size in growing pigs. The decrease in Lys, Phe, and Ile flux during ISS may be attributed to a reduction in whole-body protein synthesis or decreased catabolism of these AA. Relative to other AA, dietary Lys, Phe, and Ile requirements may decrease in ISS pigs.